(untitled) (Homoeopathy for All, 2021)
Arthritis means joint inflammation, but the term is used to describe around 200 conditions that affect joints, the tissues that surround the joint, and other connective tissue. It is a rheumatic condition. "Arthritis" is not a single disease; it is an informal way of referring to joint pain or joint disease. There are more than 100 different types of arthritis and related conditions. People of all ages, sexes and races can and do have arthritis More than 50 million adults and 300,000